Hepatic Encephalopathy after Transjugular Intrahepatic Portosystemic Shunt in Patients with Recurrent Variceal Hemorrhage - Popovič Peter; Zore Andrej; Šurlan Popovič Katarina; Garbajs Manca; Skok Pavel (Gastroenterology Research and Practice)
Purpose. The purpose of this study was to determine the incidence and predictors of hepatic encephalopathy (HE) after transjugular intrahepatic portosystemic shunt (TIPS) and endoscopic therapy (ET) in the elective treatment of recurrent variceal hemorrhage. Methods. Seventy patients were treated with elective TIPS and fifty-six patients with ET. Median observation time was 46.28 months in the TIPS group and 42.31 months in the ET group. Results. 30 patients (42.8%) developed clinically evident portosystemic encephalopathy in TIPS group and 20 patients (35.6%) in ET group. The difference between the groups was not statistically significant (P=0.542; χ2 test). The incidence of new or worsening portosystemic encephalopathy was 24.3% in TIPS group and 10.7% in ET group. Multivariate analysis showed that ET treatment (P=0.031), age of >65 years (P=0.022), pre-existing HE (P=0.045), and Child's class C (P=0.051) values were independent predictors for the occurrence of HE. Conclusions. Procedure-related HE is a complication in a minority of patients treated with TIPS or ET. Patients with increased age, preexisting HE, and higher Child-Pugh score should be carefully observed after TIPS procedure because the risk of post-TIPS HE in these patients is higher.